Novel Wastewater Treatment Applications Using Polymeric Materials - Fahim, Irene S.; Badawi, Ahmed K.; Emam, Hossam E. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on the effective removal of organic and inorganic pollutants from water and wastewater using unique freestanding polymeric-based methods. It also examines innovative green methods for efficiently reusing various solid waste products. In addition, several new eco-friendly hybrid materials are being reviewed in order to alleviate the problem of water pollution in novel, rapid, and efficient methods.